Los mecanismos de articulación y coordinación intergubernamental de Políticas Nacionales y Territoriales en el Perú - Chessman Olaechea, Yuri Alejandro (2022)
The implementation of public policies in Peru is the weakest link in the decentralization process and public management, due to the ineffectiveness of the instances, platforms or spaces of articulation and coordination where the government authorities of the three levels of government (national, regional and local) have not achieved consensus and/or agreements to establish a shared vision of territorial development in search of closing economic and social inequalities. This article presents the analysis of recent years, especially the years 2021 and 2022, on the new coordination mechanisms such as the Intergovernmental Coordination Council (CCI), which, through its operational bodies such as the Executive GORE, Executive MUNI, and Other Intergovernmental Meetings (Executive Meetings, Technical Development Tables and the Decentralized Councils of Ministers), and a new version of the Intergovernmental Commissions is presented as a new attempt to articulate national and territorial policies and strategies through effective multilevel and multi-stakeholder governance, whose purpose is to strengthen decentralized management.